Catalytic Impact of Transition Metal Ions on the Oxidation of Fragrance and Cosmetic Alcohols - Prabhu, D.V.; A. Parbat, Harichandra; Tandel, M.A. (Asian Journal of Chemistry, 2012)
The controlled oxidation of secondary cyclic alcohols, borneol, isoborneol and menthol to the corresponding carbonyl compounds has been carried out using Ce(IV) in acidic medium in the absence and presence of transition metal ions of the first series. The cyclic enantiomers borneol and isoborneol are used in the manufacture of fragrances, flavours and cosmetics. Menthol also has medicinal uses. The oxidation reaction was monitored under pseudo unimolecular conditions with respect to [Ce(IV)] in the temperature range 303-318 K. The effect of alcohol and oxidant concentrations, ionic strength and temperature on the oxidation rate have been studied. Expensive Ru(VIII), Os(VIII) and Cr(VI) ions have been exhaustively used to catalyse a variety of organic reactions. In the present study, relatively inexpensive metal ions of the first transition series have been used as effective catalysts for the oxidation of the fragrance and cosmetic alcohols under study. We have observed that the observed sequence of catalytic efficiency of metal ions does not follow the theoretically expected sequence. Suitable reaction mechanisms have been suggested for the oxidation of the alcohols in the absence and presence of transition metal ions. In absence of metal ions, the oxidation rates follow the sequence: borneol > isoborneol > menthol. The relative oxidation rates have been discussed and explained on the basis of structures, steric factors and isomeric characteristics of the fragrance and cosmetic alcohols under study.